Community Perception, Self-efficacy, and Preparedness Intention on Dam-Failure Flood Risks: A Framework - Khanm T.; Kaman Z.K.; Husin N.M.; Samsuddin S.A.; Ali Z.; Harun N.H. (Springer Science and Business Media Deutschland GmbH, 2024)
Understanding community members' perceptions is the precondition for community-based disaster risk management. Although abundant research is available in existing literature assessing flood risk preparedness and its predictive perception factors, there is a lack of research assessing such a relationship for community-based dam-failure flood risk management. The study proposed a framework for assessing community members' preparedness intentions for dam-failure flood risk by reviewing existing literature on flood risk management and other disaster risk management and taking into account dominant Protection Motivation Theory (PMT) and Person Relative to Event Theory (PrE). The proposed framework will contribute to understanding preparedness intentions for dam-failure flood risk and relevant perception factors. The suggested framework is expected to contribute to pre-hazard community-based dam-failure flood risk management by aiding plan, design, and implementation of its activities such as a risk communication program, community-based awareness, and a training program. The proposed framework includes community perception factors such as worry, perceived risk, perceived self-responsibility, and perceived outcome-efficacy as the independent variables, preparedness intention (PI) as a dependent variable, and perceived self-efficacy as the moderating variable to influence the strength of the relationship between independent variables and dependent variables. The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.